Melanopsidae (Caenogastropoda: Cerithioidea) from the eastern Mediterranean: another case of morphostatic speciation. Issue 2 (7th March 2020) - Falniowski, Andrzej; Heller, Joseph; Cameron, Robert A D; Pokryszko, Beata M; Osikowski, Artur; Rysiewska, Aleksandra; Hofman, Sebastian
Abstract: Melanopsidae were collected from 23 localities in central and south-eastern Europe, the Aegean Islands and Israel. This study considered Melanopsis from the Aegean Islands, the Peloponnese and Israel, and Esperiana esperi, Holandriana holandrii and Microcolpia from continental Europe. Shells and radulae were described and illustrated, showing continuous variation of shell characters and differences in radulae among genera. Phylogenetic analyses were conducted on single-locus datasets ( COI, 18S, 28S, ITS2 and H3 ) and on a concatenated dataset. Molecular data showed a differentiation not paralleled in morphology, reflecting morphostatic evolution. In all species with ribbed shell-forms, the ribbed and unribbed forms did not differ genetically. Within Melanopsis, four clades representing five species were distinguished. Melanopsis buccinoidea is found in Khios and Lesbos Islands, M. astropaliae in Naxos, Samos and Tinos Islands, M. wagneri in Rhodes Island and the Peloponnese, and M. costata and M. saulcyi in Israel. Molecular results and the ICZN rule of priority restrict the range of M. buccinoidea to the North Aegean Islands. ' Melanopsis ' parreyssi belongs to the genus Microcolpia . Esperiana esperi belongs to a clade separate from Microcolpia .